ACTS OF MISOGYNY AS REFLECTED IN CHO NAM-JOO’S KIM JIYOUNG, BORN 1982 - Nisfatun Palengkahu; Elisabeth Z. Oroh; Rinny Rorimpandey (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2023)
The purpose of this study is to reveal the acts of misogyny in the novel Kim Jiyoung, Born 1982, by Cho Nam-Joo. This research uses qualitative research, which is a research technique that stems from inductive thinking patterns that are based on participatory objective observation of a social phenomenon. Data were taken from the novel using a feminist approach. In addition, the researcher used Anderson's modern misogyny analysis to reveal the acts of misogyny experienced by women in the novel Kim Jiyoung, Born 1982. From this research, it can be concluded that there are four acts of misogyny experienced by women in the novel Kim Jiyoung, Born 1982. The acts of misogyny are ambivalence toward women, double standard, discrimination, and dislikeabilty of women.